Forecasting system of sales and amount of freshwater fish supply using the trend moment method - Romi Yunma Akbar; Endah Ratna Arumi; Ardhin Primadewi (Borobudur Informatics Review, 2022)
UPTD Ngrajek as a provider of freshwater fish in Muntilan, Kab. Magelang serves an average of 150,000 fish per month from tilapia, carp, tawes, catfish, catfish and carp. So, we need a system that can predict the amount of supply and demand for freshwater fish to minimize stock shortages. The Trend Moment method is used because of the advantages of using historical data that is not even or odd. The results of the application of the Trend Moment method in the forecasting system with data from December 2018 - May 2021, it is known that the error value using the MAPE test is 19.11%. This value indicates that the forecasting results on the system are good. In testing the system using alpha testing (blackbox method) and beta testing (questionnaire). 20 respondents stated that the system is easy to operate (81%), easy to transact (98%). complete information (84%), complete features (73%), forecasting information (89%), user friendly (56%), and effective (80%).